Balanced Anesthesia VS General Anesthesia for Upper Abdominal Surgery-A Comparative Study of Outcome - Zahid, M Abu; Alam, Intekhab; Haque, AKM Tanvirul; Sultana, Sharmin; Taher, SMA; Azad, AK; Raihan, Jamil (TAJ: Journal of Teachers Association, 2018)
This is a prospective randomized clinical study was done in the dept. of Rajshahi Medical College Hospital & in different Clinics in Rajshahi city from August 2013 to December 2014 to evaluate the outcome of patient undergoing upper abdominal surgery such as cholecystectomy, cholidocholithotomy, Nephrolithotomy, Gastrojejunestomy, Splenectomy, Hysterectomy, LUCS, Appendisectomy etc. by balanced anesthesia. This is also a comparative study of patient undergoing upper abdominal surgery either by balanced anesthesia or by general anesthesia. For this study 80 patients of upper abdominal surgery were randomly selected in two groups (Each group contain 40 patients) Group 'A' Patient received balanced anesthesia & group 'B' Patient received general anesthesia. Then these patient were monitored during per-operative & post operative period to evaluate its outcome. After completion of operation we have seen that those patent received balanced anesthesia had better outcome than general anesthesia undergoing upper abdominal surgery. TAJ 2012; 25: 47-54